A bibliometric analysis of global publications on graft-versus-host disease research. Issue 27 (8th July 2022) - Huang, Xuemiao; Wang, Taiwei; Zu, Wanting; Xu, Tianxin; Du, Lin; Wang, Yiming; Nie, Wenbo; Wang, Lisheng
Abstract : Background: Graft-versus-host disease (GVHD) is a fatal complication of hematopoietic stem cell transplantation and is an enormous burden on the patient economy and related health systems. Nevertheless, only a few bibliometric studies have examined the direction of research and the major findings within the field. Methods: Statistical and visualization bibliometric analysis was performed in April 2021. Our research data were retrieved from the Web of Science using an advanced search strategy. We then used bibliometric analysis to determine the current general research direction and trend of publications and established the most prolific and distinguished authors, institutions, countries, funding agencies, and keywords in GVHD research. We employed VOSviewer (Leiden University, Leiden, Netherlands), Microsoft Excel (Microsoft, Redmond, State of Washington), and GunnMap (https://lert.co.nz/map/ ) to retrieve, integrate, and visualize the results. Results: Overall, 15, 378 publications from 500 journals were extracted from the Institute for Scientific Information (ISI) Web of Science Core Collection database based on our analysis, of which the United States and the Fred Hutchinson Cancer Research Center were the most prolific countries and institutions, respectively. Moreover, we identified future research trends and the current status of GVHD research based on the top 10 most cited articles. Finally, influential authors' analysis demonstrated that Blazar, BR were both the most productive and most cited among all authors. Conclusion: Our study provides an exhaustive and objective overview of the current status of GVHD research. This information would be highly beneficial to anyone seeking information on GVHD and would serve as a reference guide for researchers aiming to conduct further GVHD research.